2016
DOI: 10.1074/jbc.m116.724393
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Evolution of Nuclear Localization Signal Sequences in Herpesvirus Terminase Subunits

Abstract: The tripartite terminase complex of herpesviruses assembles in the cytoplasm of infected cells and exploits the host nuclear import machinery to gain access to the nucleus, where capsid assembly and genome-packaging occur. Here we analyzed the structure and conservation of nuclear localization signal (NLS) sequences previously identified in herpes simplex virus 1 (HSV-1) large terminase and human cytomegalovirus (HCMV) small terminase. We found a monopartite NLS at the N terminus of large terminase, flanking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…Taking all these results together, we concluded that correct nuclear localization of both pUL51 and pUL89 requires the concurrent presence of all three terminase subunits. Conversely, pUL56 is located in the nucleus when expressed alone or in the absence of either pUL51 or pUL89, which is in accordance with the presence of a nuclear localization signal in the UL56 protein (52,53).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Taking all these results together, we concluded that correct nuclear localization of both pUL51 and pUL89 requires the concurrent presence of all three terminase subunits. Conversely, pUL56 is located in the nucleus when expressed alone or in the absence of either pUL51 or pUL89, which is in accordance with the presence of a nuclear localization signal in the UL56 protein (52,53).…”
Section: Resultssupporting
confidence: 52%
“…By applying more sensitive microscope settings, we now saw that in cells adenofected with the UL51 null genome, pUL56 was nuclear, whereas pUL89 was restricted to the cytoplasm. In general, pUL89, which does not contain a nuclear localization signal (NLS) according to in silico analyses (53), was cytoplasmic when one of the other terminase components was missing. pUL51, for which no classical NLS was predicted (53), was distributed throughout the cell in the absence of pUL56 or pUL89.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the affinity of DENV2 and 3 NS5 for importin by in vitro assay are similar while the affinity of DENV1 and 4 NS5 are weak. The differences in affinity measurement are within the expected range noted for well characterised targets such as SV40 T-ag NLS which can vary from 10–1000 nM depending on the methodolgy that is used [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 66%
“…A characteristic of HSVs is that capsids are assembled within the nucleus of infected cells (Morgan et al, 1954 ). Viral capsid proteins that are synthetized in the cytoplasm are translocated to the nucleus thanks to nuclear localization sequences (NLS) that signal these proteins to this compartment where viral genome replication takes place (Figure 3 , process 7 and Table 1 ) (Abaitua et al, 2012 ; Sankhala et al, 2016 ). HSV capsids are mainly composed of the major capsid protein VP5 and also by other less abundant viral proteins, such as VP19C, VP23, and VP26 (Thomsen et al, 1994 ; Homa and Brown, 1997 ; Kobayashi et al, 2017 ).…”
Section: Viral Capsid Assembly In the Nucleus And Transport To The Cymentioning
confidence: 99%